2019
DOI: 10.1175/bams-d-18-0180.1
|View full text |Cite
|
Sign up to set email alerts
|

Developing Priority Observational Requirements from Space Using Multi-Attribute Utility Theory

Abstract: Over a two-year period beginning in 2015, a panel of subject matter experts, the Space Platform Requirements Working Group (SPRWG), carried out an analysis and prioritization of different space-based observations supporting the National Oceanic and Atmospheric Administration (NOAA)’s operational services in the areas of weather, oceans, and space weather. NOAA leadership used the SPRWG analysis of space-based observational priorities in different mission areas, among other inputs, to inform the Multi-Attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Many experts recognize the need for this systems approach to valuation (see Helms et al, 2016;Moigne et al, 2017;NOAA 2018;Anthes et al, 2019). Agencies that deploy Earth observing (EO) infrastructure should focus their effort on developing and improving system-focused models to optimize its investments in future satellite constellations.…”
Section: Scenario 3-hurricane Evacuationsmentioning
confidence: 99%
“…Many experts recognize the need for this systems approach to valuation (see Helms et al, 2016;Moigne et al, 2017;NOAA 2018;Anthes et al, 2019). Agencies that deploy Earth observing (EO) infrastructure should focus their effort on developing and improving system-focused models to optimize its investments in future satellite constellations.…”
Section: Scenario 3-hurricane Evacuationsmentioning
confidence: 99%
“…The NSOSA study is an example in using the four identified elements of a portfolio architecture. To understand how each of the four elements comes into play it is necessary to understand a few technicalities of the NSOSA value model . The value model consists of measures of effectiveness on 38 remote sensing data collection functions and 6 strategic objectives (representing larger organizational priorities).…”
Section: Applicationsmentioning
confidence: 99%
“…The value model consists of measures of effectiveness on 38 remote sensing data collection functions and 6 strategic objectives (representing larger organizational priorities). There is a composite value function consisting of a priority weighted combination of these measures . Each system in the portfolio provides capability against a subset of the overall value model.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations